There's more to taste in a coloured bowl. - Harrar, V; Piqueras-Fiszman, B; Spence, C (2011)
The flavour and pleasantness of food and drinks are affected by their colour, their texture or crunch, and even by the shape and weight of the plate or glass. But, can the colour of the bowl also affect the taste of the food it contains? To answer this question we served popcorn in four different coloured bowls, and participants rated sweetness, saltiness, and overall liking. The sweet popcorn, in addition to being sweet, was perceived as saltier when eaten out of a coloured (as compared to a white) bowl, and vice versa for the salty popcorn. These results demonstrate that colour in bowl design can be used to elicit perceptions of sweetness and saltiness in real foods.